Geochemistry of Potential Source Rock and Natural Gas Seepages in the Mangole-Taliabu Archipelago, North Maluku, Indonesia (Rudarsko-geološko-naftni zbornik, 2023)
The Mangole-Taliabu Archipelago has great potential for natural gas exploration due to its many active natural gas seepages. The limited natural gas exploration activities initiated during the last three decades led to a lack of publications on source rock and natural gas geochemistry. Previous research has postulated that the potential source rocks in this area and its surroundings are the Buya and Salodik formations, and known active natural gas seepages are hypothesised to originate from humic organic matter (type-III kerogen). The research aims to review and re-discuss the geochemical characteristics of potential source rock, the origins and genetics of natural gas seepages, and the correlation between natural gas seepage and source rocks by integrating the existing data with the newly collected data. This research revealed that the potential source rock is the Bobong Formation, aside from the previously confirmed Buya Formation, while the Salodik Formation is not a potential source rock as was suggested in previous publications. The most significant research finding is the type of natural gas seepage which found not only coal-derived gas but also oil-type gas. The calculated Ro of the coal-derived gas source rock is 0.80% – 1.00% and that of oil-type gas source rock ranges between 0.50% – 1.31%. For gas–source rock correlation, the Bobong Formation appears to be the most likely source for RAG/88/012 and RAG/88/014 gas samples, while the Buya Formation is the source for Binono Seep, RA/21/33, RA/21/34, and RA/21/35 gas samples. The new research findings are hoped to have significant implications for increasing the understanding of the petroleum system and encouraging further exploration activities.